(untitled) (World Conference on Engineering and Technological Sciences, 2026)
The paradigm of artificial intelligence is undergoing a foundational transformation, shifting from centralized, energyintensive cloud environments toward the network edge where data is natively generated. This "Intelligence Revolution" is necessitated by the projected deployment of over 75 billion Internet of Things (IoT) devices by 2025, which renders traditional cloudcentric processing unsustainable due to latency, bandwidth, and privacy constraints.1 This research paper provides an investigation into Edge Intelligence (EI), focusing on the optimization of machine learning (ML) models for resourceconstrained hardware, including microcontrollers (MCUs) and specialized neural processing units (NPUs). We analyse the transition from the "TinyML" eracharacterized by static inference on sub100 KB modelsto a more dynamic landscape involving ondevice adaptation and federated learning on the extreme edge.3 The methodology describes the implementation of advanced optimization pipelines involving 8bit and 4bit quantization, structured pruning, and hardwareaware Neural Architecture Search (NAS). Crucially, we detail a systematic experimental workflow utilizing the MATLAB Deep Learning Toolbox and Simulink for rapid prototyping and automated C/C++ code generation for ARM CortexM hardware. Key findings demonstrate that specialized hardware accelerators can achieve speedups of up to 724x compared to pure software implementations while maintaining power envelopes below 50mW.6 Furthermore, we evaluate the impact of realtime edge AI in physical operations, noting an 80% reduction in fleet collisions and significant improvements in convergence for federated training engines.8 The paper concludes by outlining the future scope, emphasizing the convergence of 6G connectivity, green AI initiatives, and the deployment of agentic reasoning engines on mobile hardware.10